Perbandingan Hasil Pemeriksaan Hitung Jumlah Eritrosit Menggunakan EDTA Konvensional dan Vacutainer - Lilis Septiana Dewi; Tantri Analisawati Sudarsono; Retno Sulistiyowati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Hematology examination in practice often uses anticoagulants to prevent clotting in blood samples, including in the examination of the erythrocyte count. The anticoagulant that is often used for examination is EDTA (Ethylene Diamine Tetra Acetic Acid). With the changing times, the addition of anticoagulants to the examination is no longer done conventionally but is already contained in the vacutainer tube. However, the vacutainer anticoagulant cannot be adjusted to the blood volume obtained during phlebotomy, while the conventional anticoagulant can be added according to the blood volume obtained. This research is a pre-experimental research design with a One-Shot Case Study design, in which each blood sample is added with conventional anticoagulants and vacutainers. The method used is manual using a hemocytometer and a microscope. Analysis of the data using the Independent T-test. The purpose of this study was to find out the comparison of the results of the erythrocyte count using conventional EDTA and a vacutainer. After examination with both anticoagulants, p-value = 0.822 (p>0.05) so there is no comparison. Based on these results, it can be concluded that there is no comparison of erythrocyte count examination using conventional EDTA and vacutainer.